2015
DOI: 10.1016/j.mcn.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The generation of knock-in mice expressing fluorescently tagged galanin receptors 1 and 2

Abstract: The neuropeptide galanin has diverse roles in the central and peripheral nervous systems, by activating the G protein-coupled receptors Gal1, Gal2 and the less studied Gal3 (GalR1–3 gene products). There is a wealth of data on expression of Gal1–3 at the mRNA level, but not at the protein level due to the lack of specificity of currently available antibodies. Here we report the generation of knock-in mice expressing Gal1 or Gal2 receptor fluorescently tagged at the C-terminus with, respectively, mCherry or hrG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 125 publications
2
20
0
Order By: Relevance
“…However, no information is available to date whether the CB 1 receptor localizes in astroglial mitochondria as it does in mitochondria of hippocampal GABAergic and glutamatergic neurons (Bénard et al, ; Hebert‐Chatelain et al, a,b, ). In order to address this, we used conditional CB 1 receptor rescue mice re‐expressing the CB 1 receptor exclusively in astrocytic GFAP expressing cells (GFAP‐ CB 1 ‐RS), as well as CB 1 ‐WT and CB 1 ‐KO mice expressing hrGFP (De Francesco et al, ; Hadaczek et al, ; Kerr et al, ; Navarro‐Galve et al, ; Ward & Cormier, ) under the control of the GFAP promoter (GFAPhrGFP‐ CB 1 ‐WT and GFAPhrGFP‐ CB 1 ‐KO, respectively). As a first step, we determined the CB 1 receptor expression and distribution in the conditional mutant mice in order to draw the level of agreement with the CB 1 receptor expression pattern in the CB 1 ‐WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, no information is available to date whether the CB 1 receptor localizes in astroglial mitochondria as it does in mitochondria of hippocampal GABAergic and glutamatergic neurons (Bénard et al, ; Hebert‐Chatelain et al, a,b, ). In order to address this, we used conditional CB 1 receptor rescue mice re‐expressing the CB 1 receptor exclusively in astrocytic GFAP expressing cells (GFAP‐ CB 1 ‐RS), as well as CB 1 ‐WT and CB 1 ‐KO mice expressing hrGFP (De Francesco et al, ; Hadaczek et al, ; Kerr et al, ; Navarro‐Galve et al, ; Ward & Cormier, ) under the control of the GFAP promoter (GFAPhrGFP‐ CB 1 ‐WT and GFAPhrGFP‐ CB 1 ‐KO, respectively). As a first step, we determined the CB 1 receptor expression and distribution in the conditional mutant mice in order to draw the level of agreement with the CB 1 receptor expression pattern in the CB 1 ‐WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Semi-quantitative reverse transcription PCR (qRT-PCR) analysis revealed that galr2b expression was first detected at 24 hpf, and its expression was maintained in the brain and spinal cord through adulthood (data not shown). Restricted expression of galr2a and galr2b in the zebrafish CNS is very similar to mammalian galr2, indicating that zebrafish galr2a and galr2b are orthologs of mammalian galr2 [2,3,5,6,14]. In addition, widespread expression of zebrafish galr2b in the brain and spinal cord suggests that galr2b plays a role as a main receptor for galanin neuropeptides in CNS.…”
Section: Galr2a and Galr2b Is Specifically Expressed In The Zebrafishmentioning
confidence: 92%
“…In mammals, galr2 is widely expressed in the brain, including the olfactory system, preoptic area, hypothalamus, hippocampus, amygdala, pituitary gland, and brainstem [2,3,5,6,14]. To investigate the expression pattern of galr2a and galr2b in zebrafish, we first performed whole-mount in situ RNA hybridization with galr2a and galr2b.…”
Section: Galr2a and Galr2b Is Specifically Expressed In The Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation
“…Brains were postfixed in 4% PFA overnight and transferred to 30% sucrose in PBS for ~48 h. Brains were frozen in chilled isopentane and sectioned on a cryostat at 40 μm increments. Sections from the LC and paraventricular nucleus of the thalamus (PVT), which strongly expresses GalR1, 27 were stained using an adapted protocol for mCherry detection in mu opioid receptor-mCherry tagged mice. 28 See supplement for protocol ( Methods S1 ).…”
Section: Methodsmentioning
confidence: 99%